Effectiveness of Animated Films on Language Development in Early Childhood from the Mothers' Point of View - Al-Dawish, Ashwaq Alloush Saud (Journal of Educational and Psychological Sciences, 2023)
The study aimed to determine the effectiveness of animated films on language development in early childhood from the perspective of mothers in the area of Hofuf, and to achieve the goals of the study, the study followed the descriptive analytical method. A questionnaire consisting of 28 paragraphs was designed to answer the questions of the study, and the validity and reliability of the questionnaire was checked using the Half-Split method and Cronbach's alpha coefficient. The sample of the study consisted of 369 mothers of early childhood students in the Hofuf area. The study found that mothers play a role in selecting appropriate animated films that enhance language development for their children to a large extent, with an average percentage of 81.31%. The study also found that animated films are effective on language development in early childhood from the perspective of mothers to a large extent, with an average percentage of 80.76%. The results also showed that there were no statistically significant differences at the level of significance (α≤0.05) between the averages of the opinions of the sample members in the effectiveness of animated films on language development in early childhood from the perspective of mothers according to gender, and there were statistically significant differences at the level of significance (α≤0.05) between the averages of the opinions of the sample members in the effectiveness of animated films on language development in early childhood from the perspective of mothers according to the duration of the child's exposure to animated films.
Keywords: animated films; early childhood; language development